DAMPAK KENAIKAN SUKU BUNGA DAN INFLASI TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR - Agus Supriatna; Fakung Rahman; Aziz Willianta (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Many factors influence the stock price of a company, including aspects of the domestic economy. In many studies, it is explained that stock prices are very sensitive to economic indicators, including inflation and interest rates. The reason is, the two instruments cause changes in business dynamics. This study aims to reveal the impact of interest rate fluctuations and inflation on stock prices. The population in this study is data regarding interest rates, inflation, and stock prices at PT Gajah Tunggal Tbk which are included in the Central Statistics Agency (BPS), Bank Indonesia (BI) and the Indonesia Stock Exchange (BEI) for the period 2009 – 2018, using multiple regression analysis. The results revealed that the increase in interest rates had a negative impact on stock prices. This means that inflation is one of the economic factors that causes a company's stock price to decline. This happens, because inflation has an impact on people's purchasing power, so that indirectly many investors refrain from investing.